Complications and risk factors in pediatric bronchoscopy in a tertiary pediatric respiratory center. Issue 5 (2nd February 2018) - Carlens, Julia; Fuge, Jan; Price, Timothy; DeLuca, David S.; Price, Mareike; Hansen, Gesine; Schwerk, Nicolaus
Abstract: Bronchoscopy is an established procedure routinely used by pediatric pulmonologists. Despite its frequent application, data on complications and specific risk factors are scarce and sometimes conflicting. Aim: The aim of this study was to evaluate frequency and severity of clearly defined complications of bronchoscopy in children that occur both during and after the procedure, and to identify potential risk factors. Method: A retrospective single‐center analysis of 670 elective bronchoscopies in 522 children aged 0‐17 years during the time period of 2008‐2012 was performed. Procedures in intensive care unit patients and children after lung transplantation were excluded. Results: Mean patient age was 5.58 years, 61.5% had underlying chronic diseases. Intraprocedural complications occurred in 7.2% of all procedures; of these, hypoxemia was the most common, occuring in 4.8% of cases. Postprocedural adverse events were documented in 25.8%, the most frequent of which were fever in 14.2% and transient oxygen dependency in 13.4% of cases. No bronchoscopy related deaths occurred. Multivariate logistic regression was used to identify risk factors for (1) any complication, or (2) severe complications. Age below two years (OR 1.837 [1.224‐2.757], P  = 0.003) and primary ciliary dyskinesia (OR 4.821 [2.018‐11.552], P  < 0.001) significantly contributed to risk of any complication. Age below 2 years (OR 2.478 [1.072‐5.728], P  = 0.034) and underlying cardiovascular disease (OR 2.678 [1.013‐7.077], P  = 0.047) were independent risk factors for severe complications. Conclusion: Bronchoscopy in children is relatively safe. Nevertheless, adverse events can occur and knowledge of risk factors may help prevent complications.